2020
DOI: 10.1002/prca.201900090
|View full text |Cite|
|
Sign up to set email alerts
|

Deep Proteomic Insights into the Individual Short‐Term Pellicle Formation on Enamel—An In Situ Pilot Study

Abstract: Purpose: Dental pellicle formation starts instantaneously after oral hygiene due to the adsorption of salivary proteins to all orally exposed surfaces. The pellicle acts as a physiological mediator, protects the tooth surface from mechanical damages and reduces acid-induced enamel demineralization. The aim of this pilot study is to identify and characterize individual proteomic profiles of the initial pellicle formed on dental enamel and to compare the profiles with the corresponding saliva to analyze specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 54 publications
0
26
1
Order By: Relevance
“…In a recent in situ study, 498 proteins were identified in individual pellicles samples formed on bovine enamel. The higher number of identified proteins in that study is likely to be due to the much bigger surface area (8 cm 2 ) sampled and the fact that the pellicle is collected using solutions that cannot be employed in the clinical condition (25). The total number of proteins identified in situ was virtually identical to the one in vivo (170 proteins), which is lower than previously reported by VENTURA and coworkers (10).…”
Section: Discussioncontrasting
confidence: 56%
“…In a recent in situ study, 498 proteins were identified in individual pellicles samples formed on bovine enamel. The higher number of identified proteins in that study is likely to be due to the much bigger surface area (8 cm 2 ) sampled and the fact that the pellicle is collected using solutions that cannot be employed in the clinical condition (25). The total number of proteins identified in situ was virtually identical to the one in vivo (170 proteins), which is lower than previously reported by VENTURA and coworkers (10).…”
Section: Discussioncontrasting
confidence: 56%
“…Over the years, both in vitro and in vivo studies have been conducted to investigate salivary pellicle proteins. In situ salivary pellicle collection has recently been on the rise [13]. The majority of in vitro studies are carried out using hydroxyapatite or enamel slabs to form salivary pellicles with a pre-collected saliva sample, whereas in vivo salivary pellicle formation is usually carried out on freshly cleaned accessible tooth surfaces that pose a low risk of saliva contamination [4].…”
Section: In Vivo In Situ and In Vitro Salivary Pellicle Formationmentioning
confidence: 99%
“…Care should be taken for intraoral study site selection of in vivo salivary pellicles as salivary pellicle protein compositions appear to be region and site-specific [8]. A recent report by Trautmann et al [13] suggested that perhaps in situ salivary pellicle collection may enable the identification of a high number of proteins, hence it is one good choice for extensive proteomic analysis. Despite a previous report claiming notable variances in amino acid compositions between in vitro on hydroxyapatite and in vivo formed salivary pellicle [7], the variables of in vitro studies are easier to control and the results generated are considered stable and reproducible.…”
Section: In Vivo In Situ and In Vitro Salivary Pellicle Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteomic analysis revealed approximately 1000 proteins present in saliva, and approximately half of them absorbed on the tooth surface as components of forming the pellicle, displaying a highly individual proteomic profile. [ 3 ] Salivary proteins are also important in the maintenance of oral health and repair of injured oral tissues. [ 4 ] The effect of chewing on the salivary composition was considered and it was found that this process has limited effect on the composition of enzymatic proteins, mucins, and immunoglobulins in healthy individuals.…”
mentioning
confidence: 99%